THE EFFECT OF DRILL TECHNIQUE TOWARDS STUDENTS’ VOCABULARY MASTERY IN LEARNING ENGLISH - Terasne, Terasne; Hafiz, Hairori Sahrul (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
This research was aimed to answer research question “Is there any effect of Drill Technique towards students’ vocabulary mastery in learning English?” The kind of this research was an experimental research in which divided into two groups were treated with differently which experimental group was by using drill group and second control group was using three phases.  The sample of this research were all of first grade students at SMAN 1 Batulayar consisted of 75 students. This proved by figure of means group, the standard deviation and value of t-test was seen that the mean score of experimental group was higher than the mean score of control group (49.7 for the experimental and 4.47 for the control group). Based on statistical analysis using t-test showed that t-table 3.57 > 2.00 t-table at confidence level 0.05 % (95%) and 3.57 > 2.66 t-table at confidence level 0.01% (90%). Finally, it concludes that the use of Drill Technique has positive effect toward students’ vocabulary mastery in learning English at the first year students of SMAN 1 Batulayar in academic year 2021/2022.